2020
DOI: 10.1038/s41598-020-77088-w
|View full text |Cite|
|
Sign up to set email alerts
|

Morphological and cytokine profiles as key parameters to distinguish between Gram-negative and Gram-positive bacterial keratitis

Abstract: Bacterial keratitis (BK) is an ocular disorder associated with poor visual prognosis. Quantification of the associated inflammatory response may provide insight into the pathogenesis of BK and guide treatment options. In this exploratory study, we evaluated 45 BK patients and 20 healthy controls by optical coherence tomography and pro-inflammatory tear cytokine analysis. The aim was to quantify the differential morphological and cytokine inflammatory response between Gram-negative and Gram-positive BK and to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…IL-1b and TNF-a are two critical pro-inflammatory factors in the etiopathogenesis of microbial keratitis. [34][35][36][37] The antiinflammatory effect of the drug-loaded nanoparticles was assessed by ELISA kits. On day 5 after administration, the rats were executed and the corneas were excised (n = 5).…”
Section: In Vivo Corneal Penetration and Bioadhesion Assaysmentioning
confidence: 99%
“…IL-1b and TNF-a are two critical pro-inflammatory factors in the etiopathogenesis of microbial keratitis. [34][35][36][37] The antiinflammatory effect of the drug-loaded nanoparticles was assessed by ELISA kits. On day 5 after administration, the rats were executed and the corneas were excised (n = 5).…”
Section: In Vivo Corneal Penetration and Bioadhesion Assaysmentioning
confidence: 99%
“…Several animal models have studied the immunological mechanisms of ocular damage in MK (18,19). Studies on human epithelial-derived cells and gram-negative bacteria have suggested that IL-6, IL-8, and tumor necrosis factor (TNF)-α in tear are cytokines involved in immune-induced corneal damage (20,21).…”
Section: Introductionmentioning
confidence: 99%